NON-ISOTHERMAL MODELING OF SOIL VAPOR EXTRACTION SYSTEM INCLUDING SOIL TEMPERATURE EFFECT (Journal of Engineering, 2024)
Soil vapor extraction (SVE) is a proven effective in-situ technology for the removal of volatileorganic compounds (VOCs) from the subsurface. SVE process is highly sensitive to temperature.Studying annual soil temperature variation with depth declares that there is a considerable temperaturevariation in the upper few meters that may affect the overall efficiency of SVE process.A numerical model was developed to aid in investigation of field-scale soil vapor extractionprocess. The model is three-dimensional, time dependent that simulates nonisothermal vapor flow andtransport of multicomponent mixtures in soil and keeps track of the distribution of each compound inthe other three immobile phases (NAPL, aqueous, and sorbed). Rate limited interphase mass transferwith linear driving force expressions were used to model volatilization of oil into gas phase. A localequilibrium partitioning was assumed between gas, water, and solid phase. The model equations werediscretized using a standard Galerkin finite element method and solved using set iterative solutionalgorithm.Simulation of hypothetical field-scale problems was done. The physical domain described a threedimensionalsystem with flow to a single extraction well. A hypothetical soil temperature variationwith depth was incorporated with the model. The result of these simulations showed that thistemperature variation has a considerable effect on system efficiency and may play a role in optimumsystem configuration.